Simulation of the mobility of the pelvic system: influence of fascia between organs. Issue 10 (27th July 2022) - Diallo, Mouhamadou Nassirou; Mayeur, Olivier; Lecomte-Grosbras, Pauline; Patrouix, Laurent; Witz, Jean François; Lesaffre, François; Rubod, Chrystle; Cosson, Michel; Brieu, Mathias
Abstract: The mobility of pelvic organs is the result of an equilibrium called Pelvic Static characterizing the balance between the properties and geometries of organs, suspensions and support system. Any imbalance in this complex system can cause of pelvic static disorder. Genital prolapse is a common hypermobility pathology which is complex, multi factorial and its surgical management has high rate of complications. The use of 3 D numerical models and simulation enables the role of the various suspension structures to be objectively studied and quantified. Fascias are connective tissues located between organs. Although their role are described as important in various descriptions of pelvic statics, their influence and role has never been quantitatively objectified. This article presents a refine Finite Element (FE) model for a better understanding of biomechanical contribution of inter-organ fascia. The model is built from MRI images of a young volunteer, the mechanical properties derived from literature data to take into account the age of the patient and new experimental results have enabled an order of magnitude of the mechanical properties of the fascias to be defined. The FE results allows to quantify the biomechanical role of the fascia on pelvic mobility quantified by an analysis of dynamic MRI images and a local mapping of the gap between calculated and measured displacements. This improved numerical model integrating the fascias makes it possible to describe pelvic mobilities with a gap of 1 mm between numerical simulations and measurements, whereas without taking them into account this gap locally reaches 20 mm.